Islam dan Kewirausahaan: Dinamika Sosial Ekonomi Komunitas Pengrajin Batik di Karangkajen Yogyakarta (1950-1975) - Eka Yudha Wibowo (UIN Sumatera Utara Medan, 2017)
The history of Kampung Karangkajen, Yogyakarta is strongly related to batik and Muhammadiyah activity. This research is conducted to examine the socio-economy dynamics of Karangkajen’s batik industry. The major research question is why Karangkajen developed into one of the batik centers in Yogyakarta and why it showed such a high dynamic and fluctuation throughout the researched period. As seen on the previous description, the relevant research questions are; (1) who were the figures behind Karangkajen batik industry and why did they interested to engage in this business? (2) what kind of strategies were developed by the Karangkajen batik artisans and how did their religious belief affects it. Since its initial stage, Karangkajen batik industry was initiated by santri who bring their religious spirit to social, economy and politic activities. On its outgrowth, Karangkajen batik industrial went through the unstable situation. In 1950s Karangkajen batik industry revived due to Program Benteng, after its long regression since 1930 from Malaise, the turmoil period of Japanese Occupation and independence revolution. However, it doesn’t last long because the New Order’s regime withdrew the batik monopoly over GKBI in 1970s. Overall, from this business, Karangkajen batik entreupreuners – who were affiliated to Muhammadiyah mostly – managed to improve their wealth. In the meantime, they also managed to allocate some of their income for religious activity. Therefore, it is justified to say that the religious spirit implanted by Muhamaddiyah influences the economy progression of Karangkajen batik industrial. Keywords: Karangkajen, Santri Community, Muhammadiyah, Batik Artisans